Political Contestation in the Implementation of Presidential Regulation No. 59 of 2024 concerning Standard Inpatient Classes (KRIS) - Islam Manda Manggar Bumi Suharto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The implementation of the Standard Inpatient Class (KRIS) through Presidential Regulation Number 59 of 2024 represents an important reform in Indonesia’s National Health Insurance (JKN) system, aimed at promoting equitable health services for all participants. However, this policy has generated political resistance and contestation among the government, hospitals, workers’ organisations, and civil society groups. This study analyses the dynamics of political contestation in KRIS implementation using the Advocacy Coalition Framework (ACF) and Argumentative Discourse Analysis (ADA). It employs an interpretive qualitative method based on policy documents, government reports, minutes of parliamentary meetings, media publications, and supporting documents related to KRIS implementation during 2024 to 2025. The findings show that contestation occurs through three main dimensions: discourse struggles between welfare-state and market logics, negotiation and compromise within institutional arenas, and delay politics with quiet resistance at the implementation level. The shift towards a compromised three-class inpatient system reflects a negotiated agreement caused by the inability of any coalition to fully dominate the policy process. This study confirms the relevance of ACF in explaining health policy change and highlights that public policy implementation is shaped by ideas, interests, and power relations among actors.